2022
DOI: 10.1186/s12917-022-03530-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of garlic and lemon essential oils on performance, digestibility, plasma metabolite, and intestinal health in broilers under environmental heat stress

Abstract: Background Natural feed additives play an important role in poultry production due to their safety and potential properties as an antioxidant and antimicrobial, as well as a growth stimulant. The present research was designed to assess the influence of dietary supplementation of either garlic, lemon essential oil, or their mixture on performance, nutrient digestibility, plasma constituents, immunity, and oxidative status, as well as intestinal development assessed by microbiota—histomorphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 54 publications
4
28
1
Order By: Relevance
“…The lower feed intake of broiler in our research may lead to abridged weight gain and body weight following accompaniments with aqueous extract of lemon, different weight gain and feed intake of chickens led to a deterioration in the feed conversion factor of the treatments to which the aqueous extract of lemon was added during the breeding period. Our results were contrary to what was found by [19] who reported that there was an improvement in the mean body weight and the feed conversion factor of the diet added to it lemon essential oils compared to control group.…”
Section: Resultscontrasting
confidence: 99%
“…The lower feed intake of broiler in our research may lead to abridged weight gain and body weight following accompaniments with aqueous extract of lemon, different weight gain and feed intake of chickens led to a deterioration in the feed conversion factor of the treatments to which the aqueous extract of lemon was added during the breeding period. Our results were contrary to what was found by [19] who reported that there was an improvement in the mean body weight and the feed conversion factor of the diet added to it lemon essential oils compared to control group.…”
Section: Resultscontrasting
confidence: 99%
“…The results were consistent with previous investigations, by Hanieh et al (2010) who illustrated that essential oil supplementation in broilers increased the relative weights of the immune organs. A boost in the immune response and disease resistance by adding essential oil to the broiler diet has been reported in several studies (Zhang et al, 2016;Elbaz et al, 2022), which in consistent with our study. It is suggested that the antimicrobial effect of essential oils could play a beneficial role in the development of the immune system (Batiha et al, 2020), and this may be due to the effect of essential oils on increasing the available nutrients necessary for the development of the immune system.…”
Section: Immunity Responsesupporting
confidence: 93%
“…It was found that some biologically active compounds of EO reduced rate-limiting enzymes involved in cholesterol synthesis, 3 hydroxy-3-methylglutaryl coenzymes A reductase because it is a major enzyme for cholesterol production (Irawan et al, 2021). The change in lipid metabolism levels may be from the effect of essential oils antioxidants and anti-peroxide on liver activity, which affects the biosynthesis of cholesterol (Elbaz et al, 2022). These results show that the addition of clove essential oils has an effective lipid metabolism-enhancing effect by increasing lipid stability and reducing cholesterol, thus reducing lipid oxidation problems during hot climates.…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Alternative substances, including prebiotics ( Abd El-Hack et al, 2021 ; Shehata et al, 2022 ), probiotics ( Abd El-Hack et al, 2020 ; Abdel-Moneim et al, 2020a ), essential oils ( Abd El-Hack et al, 2020 ; Elbaz et al, 2022b ), traditional Chinese medicine ( TCM ) ( Dosoky et al, 2021 ; Yang et al, 2023 ), and herbal extracts ( Elbaz et al, 2021 ; Mesalam et al, 2021 ; Ebeid et al, 2023 ; Chen et al, 2024a ), as well as improved management and nutritional practices ( Abdel-Moneim et al, 2021 ; Elbaz et al, 2022a ; Siddiqui et al, 2022 ; Abdel-Moneim et al, 2023 ), offer avenues to improve bird health and productivity, obviating the necessity for AGPs. Traditional Chinese medicine and phytochemicals, in particular, have emerged as promising substitutes owing to their plant-derived compounds with immunomodulatory, antioxidant, and antimicrobial attributes.…”
Section: Introductionmentioning
confidence: 99%